Assessing video-mediated conduct: A comparison of different analytic approaches - Sellen, Abigail (Video-mediated Communication, 1997)
Decades after their introduction, video communication systems are beginning to realize their potential in supporting working from home, teaching and learning at a distance, conferencing, and interpersonal communication. In the face of an upsurge in interest, important questions are being asked: What function does video really serve, and what advantages over the telephone does it provide? How and why is video-mediated interaction different from face-to-face interaction? How can we best configure video technology to support different kinds of work at a distance? What is the role of video technology in the future? People from a variety of disciplines have now produced a substantial body of research addressing these issues from a wide range of analytic perspectives. Their results and conclusions are scattered through journals, conference proceedings, and corporate technical papers. Drawing together the ideas and findings of the major researchers in the field, this volume offers the first comprehensive overview of what is currently known about video-mediated communication. Written by psychologists, sociologists, anthropologists, engineers, and computer scientists, this book is an essential resource for all those who design and study systems for teaching, learning, and working. It is divided into four sections as follows: * Foundations surveys the literature, constructs a foundational framework, introduces common vocabulary, and helps explain technical aspects and terms. * Findings presents empirical work of types ranging from psychological laboratory-based studies to ethnographic field studies. * Design explores various aspects of the design and evaluation of new kinds of video systems. * The Future comments on new and innovative applications of video technology and points out the ways in which its use may be tied to broader technological trends.